Resumptive pronouns and code-switched A-bar dependencies: investigating the effects of optimization strategies in Egyptian Arabic/English bilinguals - Sedarous, Yourdanis; Baptista, Marlyse (Frontiers in Language Sciences, 2024)
In this paper we investigate bilinguals' sensitivity to two structures that display overlapping word orders across their two languages but are argued to have different derivational properties in their formation. We focus on filler-gap dependencies with and without resumptive pronouns in Egyptian Arabic, a language argued to have grammatical resumptive pronouns base generated at the tail end of nominal A-bar dependencies, and English, a language argued to have intrusive resumptive pronouns inserted post-syntactically due to illicit movement operations, such as in syntactic islands. Using experimental data from code-switched filler-gap dependencies, we argue that when given conflicting requirements of structural well-formedness, this population of bilinguals converge on a single structural representation across their two languages, resulting in a one-to-one mapping between derivational properties and surface form rather than maintaining two distinct representations resulting in a many-to-one mapping. To explain why bilinguals may have chosen to converge onto a unified structure rather than maintaining two distinct representations, we highlight that such one-on-one mapping is part of an arsenal of optimization strategies observable in the grammars of various bilingual populations in which bilinguals capitalize on the structural overlaps already present between their two languages. For the purpose of this paper, such optimization results in a structure that is ultimately common to both English and Egyptian Arabic, for this population of bilinguals.